@abe_daily's TikTok Content Strategy in Building Abe's Image: Strategi Konten TikTok @abe_daily dalam Membangun Citra Abe - Amru, Muhammad Nafis Ilyasa’; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2025)
Abstract. General Background: Personal branding plays a crucial role in shaping public perception and maintaining a positive reputation in the digital era. Specific Background: TikTok, with its short-video format and interactive features, offers unique opportunities for personal branding, even for children, through parental involvement. Knowledge Gap: While studies have explored influencer branding on social media, limited research examines personal branding strategies for young children developed through parental content creation. Aims: This study aims to analyze the strategies employed by Benny, as a content creator and father, in building Abe’s personal brand via the TikTok account @abe_daily. Results: Using qualitative descriptive methods and content analysis, findings reveal that Benny consistently applies eight core principles of personal branding—specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill—resulting in Abe being perceived as a humorous and active child. Novelty: This research highlights the integration of parenting values into digital branding strategies, bridging child development and media engagement. Implications: The findings provide insights for parents, educators, and digital content creators on fostering authentic, ethical, and developmentally supportive personal branding practices in online environments. Highlights: Combines parenting values with digital branding strategies. Applies eight core principles of personal branding to child content. Offers ethical insights for building authentic child personas online. Keywords: Personal Branding, TikTok, Digital Parenting, Content Strategy, @Abe_Daily